2019
DOI: 10.1101/767343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No effect of monetary reward in a visual working memory task

Abstract: ABTRACT 12 Previous work has shown that humans distribute their visual working memory (VWM) 13 resources flexibly across items: the higher the importance of an item, the better it is 14 remembered. A related, but much less studied question is whether people also have control 15 over the total amount of VWM resource allocated to a task. Here, we address this question by 16 testing whether increasing monetary incentives results in better overall VWM performance. In 17 two experiments, a total of 380 subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…While the questionnaire data suggest that subjects in gamified conditions had higher motivation than subjects in the control condition, we did not find any evidence for a difference in memory performance. This null effect on performance is consistent with earlier indications that VWM performance is not sensitive to monetary incentives (van den Berg, Zou, & Ma, 2019; Zhang & Luck, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…While the questionnaire data suggest that subjects in gamified conditions had higher motivation than subjects in the control condition, we did not find any evidence for a difference in memory performance. This null effect on performance is consistent with earlier indications that VWM performance is not sensitive to monetary incentives (van den Berg, Zou, & Ma, 2019; Zhang & Luck, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, recent modeling work theorizes that the total amount of resource dedicated to storing items in working memory is flexible and potentially able to be increased when there is more at stake (van den Berg and Ma, 2018). Prior studies on the effect of motivation on visual working memory capacity and precision have produced mixed results (Gilbert and Fiez, 2004;Krawczyk et al, 2007;Kawasaki and Yamaguchi, 2013;van den Berg et al, 2020). Here, we find that rewards do modulate working memory performance.…”
Section: Discussionmentioning
confidence: 43%
“…A number of studies have examined the influence of monetary incentives on working memory performance. Some of these studies indicate that working memory capacity is enhanced by rewards (Gilbert and Fiez, 2004;Kawasaki and Yamaguchi, 2013), while others find no effect of reward on capacity (Krawczyk et al, 2007;van den Berg et al, 2020). An additional set of studies investigating the relationship between monetary incentives and visual working memory have associated rewards with specific items in the display and have provided more definitive evidence for improved recall precision for rewarded items (Gong and Li, 2014;Klyszejko et al, 2014;Wallis et al, 2015;Thomas et al, 2016;Klink et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that reward did not facilitate the "loading" of an item into active WM to allow feature recall, and may suggest that the memory storage aspect of this task was unaffected by motivation. Previous studies have also found no benefit of reward on WM precision (van den Berg et al, 2020;Wallis et al, 2015), and others have found rewards and punishments affect item selection during WM (Fallon, Dolfen, Parolo, Zokaei, & Husain, 2019;Wallis et al, 2015). Some of these tasks used trial-wide rewards, while others used item-specific rewards, and the motivational processes will depend heavily on this as well as when the rewards were known.…”
Section: Discussionmentioning
confidence: 98%